Role Overload, Technostress, and Job Performance: The Mediating Role of Work Engagement and Burnout in Public Sector Digital Transformation - Mayora Lolly Ishimora; Fanny Martdianty (Journal of Business, Social and Technology, 2026)
Background: Focusing on the context of the implementation of the Digital Administration System X is important considering that the digital transformation of the Institution X through the PRESISI agenda has the potential to create dual work demands for personnel who must adapt technologically while maintaining operational performance. Objective: This study aims to examine the influence of role overload and technostress on the job performance of personnel in executive positions at the Headquarters of Institution X by considering the mediating role of work engagement and burnout in these relationships. Methods: A quantitative approach was used with the survey design, and data were collected from 346 implementing personnel through questionnaires. The analysis was conducted using Covariance-Based Structural Equation Modeling (CB-SEM) with LISREL 8.8 to test the direct and indirect relationships between variables. Results: The results showed that role overload and technostress had a positive effect on work engagement, consistent with the challenge-hindrance stressor framework, as well as significantly increasing burnout. Work engagement was proven to be the most dominant predictor of performance and fully mediated the influence of role overload and mediated part of the influence of technostress on job performance, while burnout was not proven to be a significant mediator. Conclusion: These findings underscore the importance of strengthening work engagement as the main psychological mechanism in ensuring the success of the Institution X digital transformation without sacrificing the welfare of personnel.